G GEOLOGI DAN KARAKTERISTIK GUNUNG LUMPUR ( MUD VOLCANO ) SUBDISTRIK OESILO, DISTRIK OECUSSE, TIMOR LESTE: GEOLOGI DAN KARAKTERISTIK GUNUNG LUMPUR ( MUD VOLCANO ) SUBDISTRIK OESILO, DISTRIK OECUSSE, TIMOR LESTE - Santi Viandi, Mardiana (ReTII, 2024)
ABSTRACT The Research Setting Is Administratively Located At Oesilo Sub-District, Oecusse, East Timor. The Research Aimed At Figuring Out The Characteristics Of Oesilo Mud Volcano In Terms Of Materials Content, Physical Appearance, And Formation Process Which Then Compared With The Surrounding Geological Condition. The Lithology Of Research Setting Is Composed Of Limestone In The Age Of Upper Miocene (N15) – Pliocene (N18). Geological Structure Becomes The Factor Or The Primary Causal For The Emergence Of Mud Volcano At Oesilo, Oecusse. It Is Anticline Structure Which Then Involved In Fault Processes Named Bend 1 And 2 Normal Right Slip Fault Directed To North And South, As Well As Native Normal Slip Fault Directed To East-West. The Analyses On Xrd, Water, Petrography, And Paleontology Reported That All Six Mud Volcanoes Have The Same Source Of Mud. The Materials Exhaled By Them Are Dense Mud And Gas, Mud With Water, Gas, And Stone Fragment. The Fossil Analysis On The Mud Indicated That The Exhaled Mud Materials Are Categorized Old. Thin Section On Some Stone Fragments Expelled Showed The Fossil Content Of Globegerinoides Obliquusbolli In The Age Of Upper Miocene – Pliocene. Keywords: Mud Volcano, Tear Faults, Oesilo, East Timor